United Apart: Gender and the Rise of Craft Unionism - Forrest, Anne (Relations industrielles / Industrial Relations, 2006)
The article reviews the book, "United Apart: Gender and the Rise of Craft Unionism," by Ileen A. DeVault.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Unionization; Women